Treatment pearls: Management of physical healthcare needs in patients with mental illness. Issue 6 (June 2022) - Miles, Leslie W.; Thatcher, Brandon; Thomas, Michael C.; Winters, Blaine
Abstract: Clinicians caring for persons with mental illness should be aware of increased mortality, physical problems, and health disparities in this population. This article provides a brief overview of physical health problems in the context of mental illness as well as those related to psychotropic medications, and discusses strategies to manage treatment effectively. Abstract : Clinicians caring for persons with mental illness should be aware of increased mortality, physical problems, and health disparities in this population. This article provides a brief overview of physical health problems in the context of mental illness as well as those related to psychotropic medications, and discusses strategies to manage treatment effectively.